Little brother - Doctorow, Cory. (New York : Tom Doherty Associates, 2008)
After being interrogated for days by the Department of Homeland Security in the aftermath of a major terrorist attack on San Francisco, California, seventeen-year-old Marcus, released into what is now a police state, decides to use his expertise in computer hacking to set things right.
"Tor."
"A Tor Teen book"--T.p. verso.
Keywords: United States. -- Dept. of Homeland Security -- Fiction; Terrorism -- Fiction; Hackers -- Fiction; Civil rights -- Fiction; Counterculture -- Fiction; San Francisco (Calif.) -- Fiction; Fiction